Factors affecting purchase behaviour of smartphone: a study on gen Y in Universiti Putra Malaysia UPM - Osman, Syuhaily; Law, Sin Yee (Malaysia Consumer And Family Economy Association (MACFEA), 2021)
Main purpose of this study was to investigate the factors affecting smartphone purchasing behaviour among Gen Y in Universiti Putra Malaysia. The factors studied were convenience, product features, social influence and brand. A total of 200 respondents participated in this study who were selected through a systematic random sampling method. Data were collected by using a self-administrated questionnaire. The Pearson correlation analysis showed that all the factors significantly influenced the smartphone purchasing behaviour among Gen Y in UPM. Meanwhile, multiple regression results indicated that product features was the strongest predictor. These findings suggested that marketers should create a suitable business plan and attractive advertisement to increase university students' smartphone purchases. In addition, future research was recommended to investigate other factors that affected smartphone purchasing behaviour among universities, mainly to gauge a more comprehensive view of Gen Y’s purchasing behaviour.